Echocardiographic abnormalities and predictors of mortality in hospitalized COVID‐19 patients: the ECHOVID‐19 study. (22nd October 2020) - Lassen, Mats Christian Højbjerg; Skaarup, Kristoffer Grundtvig; Lind, Jannie Nørgaard; Alhakak, Alia Saed; Sengeløv, Morten; Nielsen, Anne Bjerg; Espersen, Caroline; Ravnkilde, Kirstine; Hauser, Raphael; Schöps, Liv Borum; Holt, Eva; Johansen, Niklas Dyrby; et al.
Abstract: Aims: The present study had two aims: (i) compare echocardiographic parameters in COVID‐19 patients with matched controls and (2) assess the prognostic value of measures of left (LV) and right ventricular (RV) function in relation to COVID‐19 related death. Methods and results: In this prospective multicentre cohort study, 214 consecutive hospitalized COVID‐19 patients underwent an echocardiographic examination (by pre‐determined research protocol). All participants were successfully matched 1:1 with controls from the general population on age, sex, and hypertension. Mean age of the study sample was 69 years, and 55% were male participants. LV and RV systolic function was significantly reduced in COVID‐19 cases as assessed by global longitudinal strain (GLS) (16.4% ± 4.3 vs. 18.5% ± 3.0, P < 0.001), tricuspid annular plane systolic excursion (TAPSE) (2.0 ± 0.4 vs. 2.6 ± 0.5, P < 0.001), and RV strain (19.8 ± 5.9 vs. 24.2 ± 6.5, P = 0.004). All parameters remained significantly reduced after adjusting for important cardiac risk factors. During follow‐up (median: 40 days), 25 COVID‐19 cases died. In multivariable Cox regression reduced TAPSE [hazard ratio (HR) = 1.18, 95% confidence interval (CI) [1.07–1.31], P = 0.002, per 1 mm decrease], RV strain (HR = 1.64, 95%CI[1.02;2.66], P = 0.043, per 1% decrease) and GLS (HR = 1.20, 95%CI[1.07–1.35], P = 0.002, per 1% decrease) were significantly associated with COVID‐19‐related death. TAPSE and GLS remained significantly associated with the outcome after restricting the analysis to patients without prevalent heart disease. Conclusions: RV and LV function are significantly impaired in hospitalized COVID‐19 patients compared with matched controls. Furthermore, reduced TAPSE and GLS are independently associated with COVID‐19‐related death.